2018
DOI: 10.4149/bll_2018_086
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl pyruvate prevents from chronic cerebral hypoperfusion via preserving cognitive function and decreasing oxidative stress, caspase 3 activation and IL-1β level

Abstract: This study strongly imply that the EP administration can alleviate the memory impairment observed due to CCH. The protection provided by EP may result from inhibition of inflammatory response, apoptotic processes and oxidative stress (Fig. 3, Ref. 58).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…Our results indicated that MDA on POD1 was an independent risk factor for POCD, strongly suggesting a close association between oxidative stress and POCD. Excessive oxidative stress leads to lipid peroxidation of the cell membranes and the subsequent accumulation of MDA can damage brain cells, which may result in cognitive decline [13]. Pan et al demonstrated that robustly increased hippocampal MDA after surgery was significantly associated with changes in postoperative cognition [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicated that MDA on POD1 was an independent risk factor for POCD, strongly suggesting a close association between oxidative stress and POCD. Excessive oxidative stress leads to lipid peroxidation of the cell membranes and the subsequent accumulation of MDA can damage brain cells, which may result in cognitive decline [13]. Pan et al demonstrated that robustly increased hippocampal MDA after surgery was significantly associated with changes in postoperative cognition [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, no consensus has been reached about the relationship between oxidative stress and POCD until now. MDA, a bioactive aldehyde generated by free radical-mediated lipid peroxidation, is an oxidative stress marker [13]. Superoxide dismutase (SOD) is an important enzyme that catalyses the dismutation of superoxide radicals into hydrogen peroxide (H 2 O 2 ) or oxygen (O 2 ) [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is derived from pyruvate, an important metabolite in the tricarboxylic acid cycle. EP repairs tissue or cell damage and enhances immunity by anti-oxidation and reducing the secretion and expression of inflammatory factors induced by LPS such as IL-1β, IL-6 and IL-8 [11][12][13]. EP also has a therapeutic effect of repairing intestinal barrier on enteritis induced by external stimuli [14].…”
Section: Introductionmentioning
confidence: 99%
“…Önceki çalışmalar, kronik serebral hipoperfüzyonun (KSH), beyinde serbest oksijen radikallerinin (OFR) üretilmesi, glial hücrelerin aktivasyonu ve proinflamatuar sitokin yapımının artması yoluyla oksidatif stres ve inflamatuar reaksiyonu tetiklediğini göstermiştir (1)(2)(3)(4).…”
Section: Introductionunclassified